Result Turnaround Time of RT-PCR for SARS-CoV-2 is the Main Cause of COVID-19 Diagnostic Delay: A Country-Wide Observational Study of Mexico and Colombia - Isaac Núñez; Pablo F. Belaunzarán-Zamudio; Yanink Caro-Vega (Permanyer, 2022)
Background: Delay in COVID-19 diagnosis due to late real-time reverse transcription-polymerase chain reaction reporting has been described to be an important cause of suboptimal COVID-19 surveillance and outbreak containment. Objective: The objective of the study was to determine the duration of diagnostic delay due to test turnaround time and its association with marginalization status. Methods: In this observational study using national open data of Mexico and Colombia, we quantified the delay in COVID-19 diagnosis that occurred in both countries. We considered two periods that contributed to the delay in diagnosis: the time from symptom onset until testing (delay-one) and test turnaround time (delay-two). Marginalization status was determined according to country-specific scores. Results: Among 3,696,773 patients from Mexico and Colombia, delay-two was generally longer than delay-one. Median delay-one was 3 days and delay-two 7 days in Colombia, while in Mexico, they were 3 days and 4 days, respectively. In Colombia, worse marginalization status prolonged delaytwo. In Mexico, a lower number and percentage of rapid tests were performed in areas with worse marginalization. Conclusion: Diagnostic delay was mostly due to test turnaround time. Marginalization status was an important barrier to diagnostic test access.